Highly efficient hydrogen evolution reaction by strain and phase engineering in composites of Pt and MoS2 nano-scrolls. Issue 28 (5th July 2017) - Hwang, Da Young; Choi, Kyoung Hwan; Park, Jeong Eon; Suh, Dong Hack
Abstract : Our strategy begins with MoS2 sheets decorated with Pt NPs and their scrolls (called MoS2 @Pt scrolls) with intrinsic bending strain (2.4%) to provide the phase transition from the 2H to the 1T phase (28%). MoS2 @Pt scrolls have the amount of Pt NPs (8.3 wt%) and high catalytic activity (39 mV per decade). Abstract : The phase transition through local strain engineering is an exciting avenue for controlling electronic, magnetic properties and catalyst activity of materials but complex phenomenon in nanoscience. Herein, we demonstrate the first combinations of bending strain and 2H/1T phase transition by rolling up MoS2 sheets for improving catalytic activity in relatively inert basal plane surfaces and promoting electron transfer from the less-conducting 2H MoS2 sheets to the electrodes. Furthermore, we generate various MoS2 @Pt nanoparticle hybrids nanomaterials and especially MoS2 @Pt scrolls containing the coverage of Pt NPs (8.3 wt%) have a high catalytic activity (39 mV per decade). The rolled up MoS2 @Pt sheets with bending strain (2.4%) provide an intra-layer plane gliding that allows the transversal displacement of an S plane from the 2H to the 1T phases (28%). This unique combination also allows us to maximize the intrinsic HER activity among molybdenum-sulfide based catalysts.